Catalogue of fungi in China 7. New taxa of lichen-forming fungi - Qiu-Xia Yang; Hurnisa Shahidin; Li-Ting Xiao; Xu-Yun Qiu; Hui Zeng; Dorji Phurbu; Yan-Yan Wang; Xin-Li Wei (Mycology)
China has high fungal diversity and needs to be continuously explored. In this study, we focused on lichen-forming fungi and reported 18 new taxa, including one new order, viz. Polysporiales, one new family, viz. Polysporiaceae, three new genera, viz. Polysporium, Shigatsia, and Weia, and 13 new species, viz. Filsoniana fabricola, Polysporium ulmusamaroides, Psora erecta, P. nigromarginata, P. polyphylla, Shigatsia abaensis, S. daii, S. pratensis, S. qomolangmana, Umbilicaria chentangensis, U. nyalamii, Upretia xizangensis, Weia dinggyensis. Morphological, chemical, and phylogenetic analyses were comprehensively used to support the solidity of these new taxa and the accuracy of their taxonomic placements. Among the 18 new taxa, 10 were collected from Xizang Autonomous Region, China, indicating that there is a high diversity of lichen-forming fungi in the surveyed areas, and more new species are expected to be described in future studies. The addition of lichen-forming fungi in the series of Catalogue of fungi in China will not only present the lichen species diversity, but also help present the fungal diversity in China.